Wolfenbüttel 1099 Helmstadiensis (1206). W2. Facsimile-Ausgabe der Handschrift - Anonymous; Dittmer, Luther A. (Brooklyn, NY Institute of mediaeval music, 1960)
Wolfenbüttel 1099 Helmstadiensis(1206). W2. Facsimile Reproduction of the Manuscript. With an Introduction by Luther Dittmer. Publications of Mediaeval Musical Manuscripts, 2. Brooklyn, 1960-69 13 x 19 cm, 12, 507 pp. Superb collotype in original format. The second largest repository of Notre Dame music with organum, conductus and motet.